Percutaneous Trans-septal Mitral Valve-in-Ring Implantation Using a Transcatheter Balloon-Expandable Transcatheter Heart Valve With Elective Intra-Procedural Artero-Venous ECMO in a Patient With Severely Reduced Left Ventricular Ejection Fraction - Ristalli, Francesca; Maiani, Silvia; Hamiti, Brunilda; Mattesini, Alessio; Meucci, Francesco; Stolcova, Miroslava; Di Mario, Carlo (Frontiers in Cardiovascular Medicine, 2019)
Percutaneous mitral valve-in-valve implantation is an emerging option in patients with surgical bioprosthesis failure or failing mitral annuloplasty and increased surgical risk. We present a case of transcatheter transvenous trans-septal mitral valve-in-ring procedure, in a patient with severe left ventricular dysfunction and severe mitral regurgitation, after surgical mitral annuloplasty, managed with periprocedural mechanical circulatory support with VA-ECMO.